Breeding estimation of the winter wheat varieties in the conditions of the southern forest-steppe of Western Siberia - I. V. Pototskaya; S. S. Shepelev; A. S. Chursin; A. M. Kovalchuk; V. P. Shamanin (Зерновое хозяйство России)
The expansion of winter wheat sowing areas is one of the reserves for increasing grain production in the Siberian region, since the areas under winter wheat is 15–20 % larger than under spring wheat according to productivity and has great potential in using bioclimatic resources of the region. the availability of sources of economically valuable traits and the development of various initial material on their basis is of decisive importance for breeding of new winter wheat varieties and their successful introduction into production. The purpose of the current paper was to find sources of economically valuable traits from the collection of winter wheat varieties of Russian breeding in the conditions of Western Siberia. There has been studied a collection of varieties and lines of winter common wheat of Russian breeding from the institutions of the Rostov region, Stavropol, and Krasnodar Areas. Field and laboratory trials were carried out on the experimental field of the Omsk SAU in the conditions of the southern forest-steppe of Western Siberia in 2020–2022. Sowing was laid in fallow at the generally accepted sowing dates. According to the breeding estimation of the studied samples in the field seasons of 2020–2022 there was a significant correlation between winter resistance of plants and winter wheat productivity (r = 0.59), as well as an inverse correlation between productivity and gluten percentage (r = –0.36), grain ash content (r = –0.73) and sedimentation (r = –0.38). The varieties ‘Barynya’ (North Caucasian FNAC), ‘Gubernator Dona’, ‘Donna’ (Rostov ARC), ‘Don 107’, ‘Nakhodka’ (ARC “Donskoy”) and the line ‘K18918’ (RCG named after P.P. Lukyanenko), characterized by increased winter resistance (6.5–8 points) and productivity (351–384 g/m2) have been recommended as sources in breeding to improve productivity level and stability of winter wheat varieties in the conditions of Western Siberia. The varieties ‘Etnos’, ‘Anka’, ‘Gurt’, ‘Antonina’, ‘Alekseich’ and ‘Duplet’ of Krasnodar breeding with a high protein and gluten percentage (16.1–17.9 % and 35.5–39.3 %), large grain ash content and sedimentation (1.59–1.92 % and 58.0–67.0 ml) can be used as an initial material in breeding to improve the quality of winter wheat grain.